LANGUAGE REPRESENTATIONS AS A FORM OF SOCIAL KNOWLEDGE - Lina Vasilyevna Razumova (Science and Innovation Center Publishing House, 2020)
The article is devoted to clarifying the nature of language knowledge in the system of social knowledge. Social representation is a complex cognitive structure. As a social form of knowledge of social representation is used for the interpretation of social reality. It allows us to understand and analyze the regulatory effect of the social system on the cognitive domain of a social group, an individual. The author aims to clarify the main characteristics of language representation and its structure as a form of social knowledge. The relevance of the article is determined, on the one hand, by the increased interest in cognitive developments that can reveal complex mechanisms of categorization of human knowledge. On the other hand, we are talking about the author’s attempt to apply the psychological concept of representation to clarify the psychosocial characteristics of language knowledge, in particular, ideas about the language norm as a form of social knowledge.